2022
DOI: 10.1093/bib/bbac030
|View full text |Cite
|
Sign up to set email alerts
|

SAM-TB: a whole genome sequencing data analysis website for detection of Mycobacterium tuberculosis drug resistance and transmission

Abstract: Whole genome sequencing (WGS) can provide insight into drug-resistance, transmission chains and the identification of outbreaks, but data analysis remains an obstacle to its routine clinical use. Although several drug-resistance prediction tools have appeared, until now no website integrates drug-resistance prediction with strain genetic relationships and species identification of nontuberculous mycobacteria (NTM). We have established a free, function-rich, user-friendly online platform for MTB WGS data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…In our results, web-based tools enabled an effective and user-friendly identification of resistanceassociated mutations in M. tuberculosis. The recently developed SAM-TB platform [21] is the most capable of determining the mutations present in the isolates of our study, which, when used in conjunction with web-based tools Mykrobe and PhyReSse, would allow rapid screening of M tuberculosis isolates. These tools could easily be implemented in surveillance programs based on microbiological procedures to obtain results efficiently and cheaply [84,87,88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our results, web-based tools enabled an effective and user-friendly identification of resistanceassociated mutations in M. tuberculosis. The recently developed SAM-TB platform [21] is the most capable of determining the mutations present in the isolates of our study, which, when used in conjunction with web-based tools Mykrobe and PhyReSse, would allow rapid screening of M tuberculosis isolates. These tools could easily be implemented in surveillance programs based on microbiological procedures to obtain results efficiently and cheaply [84,87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Although these methods are rapid and straightforward, Mtb continuously evolves through the genomic acquisition of single nucleotide polymorphisms (SNPs), insertions, and deletions (indels), impacting the ability to discriminate strains without the classic regions used for resistance detection [ 20 ]. Whole-genome sequencing (WGS), as a molecular diagnostic tool, has been greatly developed in TB research and is clinically useful for predicting drug resistance, lineage, tracing transmission, and defining outbreaks [ 21 26 ]. Furthermore, WGS has the potential to determine drug resistance much faster than traditional phenotypic drug susceptibility testing (DST) [ 27 ] and does not require biological safety infrastructure [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the low cell wall permeability of mycobacteria and the different efflux pump systems or porin channels, could also play a crucial role in intrinsic drug resistance in NTMs such as M. fortuitum or M. smegmatis (van Ingen et al, 2012; Bakuła et al, 2018) and could explain the intrinsic resistance to isoniazid found in M. brumae . Finally, similar to isolates of M. fortuitum and M. avium complex (Cheng et al, 2017), M. brumae is also resistant to p-aminosalicylic acid, although the mutations responsible for resistance have not been specifically identified (Yang et al, 2022). Thus, due to the differences in drug resistance genetic determinants among Mycobacterium species, additional efforts are needed to determine drug susceptibility by molecular approaches in NTM as M. brumae .…”
Section: Discussionmentioning
confidence: 99%
“…The MDR-TB strains were recultured and sequenced as previously described ( 20 ). The raw data were uploaded to the Mycobacterium tuberculosis WGS data analysis platform (SAM-TB) ( 21 ) for quality control, detection of known resistance-associated mutations, lineage identification, pairwise single-nucleotide polymorphism (SNP) distance calculation, and construction of phylogenetic trees. For molecular DST, SAM-TB integrates drug-resistance mutation sets from the CRyPTIC Consortium/100,000 Genomes Project and the TB-Profiler tool ( 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%